PPARγ Agonist Rosiglitazone Suppresses Renal mPGES-1/PGE2 Pathway in db/db Mice. (30th December 2013) - Sun, Ying; Jia, Zhanjun; Liu, Gang; Zhou, Li; Liu, Mi; Yang, Baoxue; Yang, Tianxin
Abstract : Evidence had shown the detrimental effect of prostaglandin (PG) E2 in diabetic nephropathy (DN) of STZ-induced type-1 diabetes but its role in the development of DN of type-2 diabetes remains uncertain. The present study was undertaken to investigate the regulation of PGE2 synthetic pathway and the interaction between peroxisome proliferator-activated receptor (PPAR) γ and PGE2 synthesis in the kidneys of db/db mice. Strikingly, urinary PGE2 was remarkably elevated in db/db mice paralleled with the increased protein expressions of COX-2 and mPGES-1. In contrast, the protein expressions of COX-1, mPGES-2, cPGES, and 15-hydroxyprostaglandin dehydrogenase (15-PGDH) were not altered. Following 1-week rosiglitazone (Rosi) therapy, urinary PGE2, but not other prostanoids, was reduced by 57% in parallel with significant reduction of mPGES-1 protein and EP4 mRNA expressions. By immunohistochemistry, mPGES-1 was significantly induced in the glomeruli of db/db mice, which was almost entirely abolished by Rosi. In line with the reduction of glomerular mPGES-1, the glomerular injury score showed a tendency of improvement after 1 week of Rosi therapy. Collectively, the present study demonstrated an inhibitory effect of PPAR γ activation on renal mPGES-1/PGE2/EP4 pathway in type-2 diabetes and suggested that mPGES-1 may potentially serve as a therapeutic target for treating type-2 diabetes-associated DN.